Pemanfaatan Aromaterapi Jahe terhadap Perubahan Tekanan Darah, Tingkat Stres, dan Tingkat Kenyamanan pada Ibu Hamil Berisiko Preeklamsia - Mufida Annisa Rahmawati; Fitria Aisyah; Eti Kuswandari; Woro Tri Utami (Mando Care Jurnal, 2026)
Preeclampsia is a pregnancy complication characterized by elevated blood pressure and contributes significantly to maternal and fetal morbidity. Non-pharmacological interventions based on local wisdom, such as ginger aromatherapy, have the potential to serve as complementary therapy in improving maternal health outcomes. This study aimed to analyze the effect of ginger aromatherapy on changes in blood pressure, stress levels, and comfort levels among pregnant women at risk of preeclampsia. This study employed a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 30 pregnant women at risk of preeclampsia selected using purposive sampling. The intervention was administered through inhalation of ginger aromatherapy. Measurements were conducted before and after the intervention on blood pressure, stress levels, and comfort levels. Data were analyzed using paired t-test, followed by mean difference (MD), 95% confidence interval (CI), and effect size (Cohen’s d) analyses. The results showed a significant reduction in systolic blood pressure (MD = -12.40; 95% CI: -14.80 to -10.00; p=0.001; d=1.25) and diastolic blood pressure (MD = -8.20; 95% CI: -9.90 to -6.50; p=0.001; d=1.18). Stress levels also decreased significantly (MD = -5.60; 95% CI: -7.10 to -4.10; p=0.002; d=1.05), while comfort levels increased significantly (MD = 12.20; 95% CI: 9.80 – 14.60; p<0.001; d=1.30). Conclusion is Ginger aromatherapy significantly reduces blood pressure and stress levels while improving comfort among pregnant women at risk of preeclampsia. This intervention may be recommended as a complementary therapy based on local wisdom in midwifery care.